Przyczyny upadku małych firm na terenach zmarginalizowanych - Lisowska, Renata; Ropęga, Jarosław (The Reasons of Small Firms' Failure in the Marginalized Areas, 2009)
Companies in the marginalized areas have a different business environment compared to other sites. There are difficult conditions for the growth and development. The article describes the characteristics of the marginalized areas and factors affecting the development of the changing environmental conditions. The authors also presents the analysis of the causes of the deterioration of the situation of companies in the marginalized areas, both in the field of environment and internal processes of a company. Then, they analyze the symptoms which can cause the crisis and, consequently, lack of the firm's response. The study presents paths of economic failures of these companies in the marginalized areas. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 707-715